2008
DOI: 10.1177/0093854808316487
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Media Violence Exposure On Criminal Aggression

Abstract: The article presents a meta-analysis of studies—yielding 26 independent samples of subjects—on the relationship between exposure to media violence and violent aggression. Mean effect sizes from aggregate and experimental studies do not suggest that media violence and criminal aggression are positively associated, but findings from prospective longitudinal studies are more ambiguous. Summary statistics based on models strictly conforming to each study's original design were compared to post hoc models (in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 56 publications
4
92
0
3
Order By: Relevance
“…Although much debate remains on the role of media violence on youth aggression, our results support the view voiced by some that efforts to regulate media violence may not be particularly helpful in reducing youth violence. [31][32][33][34][35] Finally, positive family relations were also a fairly inconsistent predictor of youth aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Although much debate remains on the role of media violence on youth aggression, our results support the view voiced by some that efforts to regulate media violence may not be particularly helpful in reducing youth violence. [31][32][33][34][35] Finally, positive family relations were also a fairly inconsistent predictor of youth aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this claim is strengthened by findings from longitudinal (Williams & Skoric, 2005) and other published meta-analytic studies that show little to no relationship between violent video game play and aggression (Ferguson, 2007;Savage & Yancey, 2008;Ferguson & Kilburn, 2010).…”
mentioning
confidence: 92%
“…A number of studies have linked violent video games to negative outcomes, including aggression (Anderson, 2004) and delinquency (Exelmans, Clusters, & Van den Bulck, 2015). Other analyses, have, however, shown no effect of violent video gaming on these and other negative outcomes (Ferguson, Olson, Kutner, & Warner, 2014;Ferguson et al, 2008;Savage & Yancey, 2008). Recently, Morris and Johnson (2014) found that adolescents with deviant peers who spent time playing video games of any type were not at risk for violence or general delinquency.…”
Section: Discussionmentioning
confidence: 99%